Design of athermal arrayed waveguide grating using silica/polymer hybrid materials - Li, De-Lu; Ma, Chun-Sheng; Qin, Zheng-Kun; Zhang, Hai-Ming; Zhang, Da-Ming; Liu, Shi-Yong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
This study demonstrates a novel athermal arrayed waveguide grating (AWG) which is composed of silica/polymer hybrid materials on a silicon substrate. The temperature-dependent wavelength shift of the AWG depends on the refractive indices of the materials and the size of the waveguide. The athermalization of the AWG can be realized by selecting the proper values of the material and structural parameters of the device.
Optica Applicata, Vol. 37, 2007, nr 3, s. 305-312
Keywords: optyka; arrayed waveguide grating; temperature-dependent wavelength shift; athermalization